Exploration and Innovation in Addressing Maternal, Infant and Neonatal Mortality - Khanal, L; Dawson, P; Silwal, R C; Sharma, J; KC, N P; Upreti, S R (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The Government of Nepal has been remarkably progressive in introducing innovative community-based maternal newborn and child health interventions in an effort to address the major causes of maternal and child mortality in the country. This article describes the introduction of innovative interventions, including a review of the landmark research that precipitated the discussion and provided evidence of practical feasibility, the acceptance of the intervention concept and validity, the approval process and the introduction and results from the pilot interventions. These interventions, which include the use of misoprostol to prevent post partum haemorrhage during homebirths, Morang Innovative Neonatal Intervention, gentamicin in Uniject and for the management of neonatal sepsis and newborn vitamin A supplementation, are in various stages and demonstrate the responsiveness of the Government to new approaches that address the major causes of maternal and child mortality. Keywords: chlorhexidine; gentamicin in Uniject; innovations; misoprostol; Morang Innovative Neonatal Intervention; Nepal; newborn vitamin A supplementation. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>